Avaliação genética, parâmetros genéticos e fenotípicos do peso ao nascer de suínos - Lima, Paulo Sérgio Silva (Universidade Federal do Tocantins, 2021)
The aim of this study was to estimate the genetic and phenotypic parameters for characteristic birth weight in cross-bred pigs. The experiment was carried out in the Pig Industry Sector of the School of Veterinary Medicine and Zootechnics at the Federal University of Tocantins, Campus de Araguaína-TO, the weights of 52 piglets born between February and August 2019, children of 5 females (1 Duroc, 1 mixed breed, 3 Pietrain) and 2 males (Pietrain). Estimates of genetic and phenotypic parameters for birth weight were made using a uniquely characteristic animal model. Heritability values of 0.6615 and 0.0282 were found, for birth weight without adding the maternal effect and with maternal effect, respectively, and the maternal genetic variance proportion value in relation to the total variation (m²) of 0.4552.